Induction Of Luteolysis In Buffaloes Using A Micro Dose Of Pgf2α Along With Acupuncture - Shah, R.G.; Makwana, P.M.; Kelawala, N.H.; Joshi , R.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A study was conducted on the effect of administration of micro dose of prostaglandin at the BAI HUI acupuncture point for luteolysis and oestrus induction in Surti Buffaloes. The study revealed significant decrease in the concentrations of progesterone at 24 h and 48 h after treatment in buffaloes treated with micro dose of PGF2α at the BAI HUI acupuncture point as compared with control group of buffaloes.
Keywords: BAI HUI; Acupoint; Buffaloes; Luteolysis; Progesterone; Prostaglandin